Biomimetics in Human Immunology and Applications - Tung, Bui Thanh; Hai, Nguyen Thanh; Huyen, Nguyen Thi; Hien, Tu Thi Thu; Hue, Pham Thi Minh (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 34 No 1DO - 10.25073/2588-1132/vnumps.4117, 2018)
As a scientific discipline, biomimetics has potential applications in various research fields for improving human lives. The advances in research on human and animal immune systems and immunological mechanisms have helped develop a lot of approaches in preventing, diagnosing, and treating diseases. By studying the biomimetic models and materials mimicking the components of those systems, we have advanced our knowledge and skills in developing new products for pharmaceutical and medical applications. Therefore, immunology and biomimetics of immune systems may have limitless potential applications in health sciences. This review focuses on the application of biomimetic antibodies and monoclonal antibodies to the diagnosis and treatment of diseases. Keywords Biomimetics, monoclonal antibody, immune system. References[1] Hwang Jangsun, Jeong Yoon, Park Jeong Min, Lee Kwan Hong, Hong Jong Wook, Choi Jonghoon, Biomimetics: forecasting the future of science, engineering, and medicine, International Journal of Nanomedicine 10 (2015) 5701-5713. [2] Nguyễn Thanh Hải, Bùi Thanh Tùng, Phạm Thị Minh Huệ, Phỏng sinh học trong y dược học – Hướng nghiên cứu cần được đẩy mạnh, Tạp chí Khoa học Đại học Quốc gia Hà Nội – Khoa học Y Dược 33(1) (2017) 1. [3] Từ Minh Koóng, Nguyễn Thanh Hải, Thuốc tới đích, Tạp chí Dược học 389(9) (2008) 2. [4] Candy S Hwang, Lauren C. Smith, Yoshihiro Natori, Beverly Ellis, Bin Zhou, Kim D Janda, Efficacious Vaccine against Heroin Contaminated with Fentanyl, ACS Chemical Neuroscience, Just Accepted Manuscript, Publication Date (Web): 20 Mar 2018. [5] Abul K. Abbas, Andrew H. Lichtman,Shiv Pillai, Basic Immunology: Functions and Disorders of the Immune System, fouth edition 1-22. [6] Borghesi L, Milcarek C, From B cell to plasma cell: regulation of V(D)J recombination and antibody secretion, Immunol Res36 (1–3)(2006) 27–32. [7] Alisa M. Campbell, Monoclonal Antibody and Immunosensor Technology: The production and application of rodent and human monoclonal antibodies(1991) 1-7 21-42. [8] James W. Goding, Monoclonal Antibodies: Principles and Practice, third edition, 116-129. [9] John R. Birch, Andrew J. Racher, Antibody production, Advanced Drug Delivery Reviews 58 (2006) 671 – 685. [10] Adriana R. Marques, Laboratory Diagnosis of Lyme Disease - Advances and Challenges, Infectious Disease Clinics of North America29(2) (2015) 295–307. [11] Linde A, Diagnosis of Epstein-Barr virus-related diseases, Scandinavian journal of infectious disease 100 (1996) 83-8. [12] Stern P, Current possibilities of turbidimetry and nephelometry,Klin Biochem Metab, 14 (3) (2006) 146–151. [13] Douglas B. Cines, Alan D. Schreiber, Immune Thrombocytopenia — Use of a Coombs Antiglobulin Test to Detect IgG and C3 on Platelets, The New England Journal of Medicine 300 (1979) 106-111. [14] William J. Payne, JR., David L. Marshall, Robert K. Shockley, William J. Martin, Clinical laboratory applications of monoclonal antibodies, Clinical Microbiology Review 1(3) (1988) 313–329. [15] Zhang X, Soori G, Dobleman TJ, Xiao GG, The application of monoclonal antibodies in cancer diagnosis, Expert Rev. Mol. Diagn. 14(1) (2014) 97–106. [16] Erik A. Rodriguez, Ye Wang, Jessica L. Crisp, David R. Vera, Roger Y. Tsien, Richard Ting, New Dioxaborolane Chemistry Enables [18F]-Positron-Emitting, Fluorescent [18F]-Multimodality Biomolecule Generation from the Solid Phase, Bioconjugate Chemistry 27 (5) 1390–1399. [17] Waldmann TA, Monoclonal antibodies in diagnosis and therapy, Science 252(5013) (1991) 1657-62. [18] M. Z. Siddiqui, Monoclonal Antibodies as Diagnostics; an Appraisal, Indian Journal of Pharmaceutical Sciences 72(1) (2010) 12–17. [19] Urbaniak S, Greiss M, RhD haemolytic disease of the fetus and the newborn, Blood Rev 14 (1) (2000) 44–61. [20] Fung Kee Fung K , Eason E , Crane J , Armson A , De La Ronde S , Farine D , Keenan-Lindsay L , Leduc L , Reid GJ , Aerde JV , Wilson RD , Davies G , Désilets VA , Summers A , Wyatt P , Young DC , Prevention of Rh alloimmunization, Journal of Obstetríc and Gynaecology Canada25 (9) (2003) 765–73. [21] Klinguer-Hamour C, Caussanel V, Beck A, Monoclonal antibodies for treating infectious diseases, Medecine sciences 25(12) (2009) 1116-20. [22] Erin Sparrow, Martin Friede, Mohamud Sheikh, Siranda Torvaldsenc, Therapeutic antibodies for infectious diseases, Bulletin World Health Organization 95(3) (2017) 235–237. [23] Joseph Thomas Pento, Monoclonal Antibodies for the Treatment of Cancer, Anticancerresearch 37(2017) 5935-5939. [24] Andrew M. Scott, James P. Allison, Jedd D. Wolchok, Monoclonal antibodies in cancer therapy, Cancer immunity 12 (2012) 14. [25] A Coulson, A Levy, M Gossell-Williams, Monoclonal Antibodies in Cancer Therapy: Mechanisms, Successes and Limitations, West Indian Medical Journal 63(6) (2014) 650-654. [26] Henri Kreis, Christophe Legendre, Lucienne Chatenoud, OKT3 in organ transplantation, Transplantation Reviews 5(4) (1991) 181–199. [27] A, Purtscher M, Muster T, Ballaun C, Buchacher A, Sullivan N, Srinivasan K, Sodroski J, Moore JP, Katinger H, Human monoclonal antibody 2G12 defines a distinctive neutralization epitope on the gp120 glycoprotein of human immunodeficiency virus type 1, Journal of Virology 70(2) (1996) 1100-1108. [28] Ann L.Daugherty, Randall J.Mrsny, Formulation and delivery issues for monoclonal antibody therapeutics, Advanced Drug Delivery Review 58 (5-6) (2006) 686-706. [29] J Mimuro,Y Koike, Y Sumi, N Aoki, Monoclonal antibodies to discrete regions in alpha 2-plasmin inhibitor, Blood 69 (1987) 446-453. [30] Eloy JO, Petrilli R, Trevizan LNF, Chorilli M, Immunoliposomes: A review on functionalization strategies and targets for drug delivery, Colloids and Surfaces B: Biointerfaces 159 (2017) 454-467. [31] Rang, H. P, Pharmacology(2003) 241 Edinburgh: Churchill Livingstone